Saline nasal irrigation and gargling in COVID-19: Part II. Outcomes in Omicron and risk–benefit for self-care - S. Huijghebaert; C. Fabbris; C. Fabbris; A. L. Baxter; S. Parviz; U. S. Chatterjee; D. Rabago (Frontiers in Public Health)
BackgroundThe World Health Organization recommends at-home management of mild COVID-19. While our preliminary evaluation provided evidence for saline nasal irrigation (SNI) and gargling in COVID-19, an update and risk–benefit assessment for self-care in Omicron infection is warranted, from treatment and preparedness perspectives, as new SARS-CoV-2 variants continuously emerge, while symptoms overlap with those of common colds and other upper respiratory tract infections.MethodsSystematic literature searches for preclinical and clinical studies involving Omicron infection and saline, bias assessment, and review of outcomes (benefits, risks).ResultsA total of 14 studies met eligibility criteria: one experimental proof-of-concept study, eight randomized clinical trials (RCTs), two quasi-experimental, two matched case–control, and one controlled study (2,389 patients, 1,101 receiving saline). Study designs were highly heterogeneous, not allowing pooling of the data. In line with the pre-clinical findings, the clinical trials showed lower viral loads or faster viral clearance with SNI use; results were consistent, if SNI was started early in the infection. Individual studies supported reduced infectivity of saliva, inflammatory mediators and C-reactive protein, and increased lymphocytes. Symptoms resolved faster if severe at baseline, in line with the findings from pre-Omicron RCTs; the ability to perform daily activities was assessed in one RCT and improved significantly. Early initiation of daily SNI/gargling before the onset of smell/taste dysfunction prevented their development. Daily SNI hygiene was also associated with less frequent development of fever and a shorter duration of fever than observed among (non-irrigating) controls. Daily SNI modestly helped to reduce household transmission; a preliminary report suggests that reliable prophylaxis can be achieved, provided daily SNI is combined with strict use of personal protective measures. Hospitalization was virtually absent. Isotonic SNI was best tolerated.ConclusionThis analysis is consistent with prior review findings: early initiation of SNI/gargling may help patients with mild COVID-19 feel better, irrespective of the variant. If clean water and irrigation materials are provided, SNI can reasonably be recommended as early self-care for COVID-19, as it is for the common cold. Larger prospective studies are required to determine optimal protocols and SNI’s potential role in respiratory pathogen pandemic preparedness.